A Meandered Inductive Loop based RFID Tag Antenna at 866 MHz - Singh A.K.; Singh A.K. (My University, 2025)
In this article, a regular tag antenna supporting UHF band RFID composed of spiral-ending meander-line with meandered inductive loop is depicted. This portrayed novel compact spiral-ending meandered tag with dual sided meandered inductive loop microstrip dipole cuts down the area of tag antenna plus provides an upgraded conjugate impedance-matching amid tag and semiconductor ASIC. Aforementioned tag antenna serves at 866 MHz. A predominating compact UHF tag confining the extents of 60mm× 16mm× 1.6mm(0.173λ× 0.046λ× 0.0046λ), retaining impressive reflection coefficient has been elegantly testified and it is competent to access recognition territory of 12.6 m. Presented tag antenna layout is simulated in favor of 4 W EIRP reader. © 2023 IEEE.